Bukavu - Rosa, Helvy Tiana, 1970-; Prast, Taufan E. (Depok, Indonesia: PT Lingkar Pena Kreativa, 2008)
Biography of Agus Salim, Malaysian writer.
In Malay.
Short stories.
Koleksi Sumbangan : Abdul Ghafar Ibrahim
Keywords: Short stories, Indonesian